The Effect of Supervision and Transparency Management of Village Funds on Community Trust in Kampung Yahim Jayapura District - Brian Alessandro Orno; Agustinus Salle; Klara Wonar (Journal Research of Social Science, Economics, and Management, 2025)
Public trust in village governance is crucial for sustainable development, particularly in the management of village funds. However, issues such as lack of transparency and weak supervision in Kampung Yahim, Jayapura Regency, have raised concerns about fund misallocation and eroded community confidence. Addressing these challenges is essential to ensure accountability and foster trust in local governance. Using a quantitative approach, this research employs multiple linear regression analysis on data collected from 96 respondents selected via purposive sampling. Primary data were gathered through a Likert-scale questionnaire, measuring supervisi (X1), transparansi (X2), and community trust (Y). Statistical analysis was conducted using SPSS 22, including normality, multicollinearity, and heteroscedasticity tests to validate the regression model. The results of the research indicate that supervisi and transparansi in the management of village funds influence community trust in Yahim Village, Sentani District, Jayapura Regency. Effective supervisi and transparansi in village fund management are critical for building and maintaining community trust. Strengthening these aspects can mitigate misuse of funds and promote greater public engagement in local governance. The research recommends that village authorities enhance accountability mechanisms, such as regular audits and open financial reporting, to reinforce trust. Policymakers should institutionalize participatory monitoring systems to ensure sustainable and transparent fund management. These measures can serve as a model for improving governance in similar rural contexts.